High performance of electrochemical sensors based on LbL films of gold nanoparticles, polyaniline and sodium montmorillonite clay mineral for simultaneous detection of metal ions - de Barros, Anerise [UNESP] (2017)
We report the effects of the incorporation of gold nanoparticles (AuNPs) into LbL films of emeraldine salt polyaniline (PAni-ES) and sodium montmorillonite clay mineral (Na+-MMT). We observed the higher performance of electrochemical sensors was induced by AuNPs towards trace level detection of cadmium (Cd2+), lead (Pb2+) and copper (Cu2+) ions. The detection was performed by square wave anodic stripping voltammetry (SWASV) using ITO electrodes modified with LbL films composed of three supramolecular architectures: PAni-ES/AuNPs, AuNPs/Na+-MMT and PAni-ES/AuNPs/Na+-MMT, which were compared to the LbL films without AuNPs. The results are consistent with the AFM dates indicating that the increase of roughness favors at low limit of detection for the sensors. The incorporation of AuNPs and PAni-ES leads to an interaction via ion-dipole, as characterized by FTIR and Raman spectra. This interaction, consequently, causes a more extended polymer chain, which intercalate into Na+-MMT galleries, according to X-ray diffraction data. The results demonstrate the possible control of film properties by exploiting molecular-level interactions in multicomponent nanostructured films favoring directly in electrochemical sensors response.